A Review on Sanitary Models and Water Drainage Systems from Ancient Mesopotamia - Dr. Mohammad Sabri AbdulRaheem; Prof. Raghad AbdulQadir Abbas (المجلة العربية للدراسات الانسانية والاجتماعية, 2026)
Archaeological excavations provide us with a lot of information and evidence that guide us realize the facts, ideas and practices of various forms and patterns related to several aspects of human life such as: worship, industries, social relations and arts, where architecture is considered a kind of arts in which man excelled. It could be surprising to know that in some parts of the world people might have lacked such a service facility in human life until the eleventh century AD. Some archaeologists attribute complex and elaborate water drainage systems, discovered in some structural units of ancient Iraq, to the civilization of (Mohenjedaro) in the Indus Valley, while many archaeological sites abound with different models of them showed complex designs, came to us from periods preceded the Sumerian age (early third millennium BC) and continued to a late period of Mesopotamia history.